2021
DOI: 10.1557/s43577-021-00170-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance of three-dimensional printed nasopharyngeal swabs for COVID-19 testing

Abstract: At the start of the COVID-19 pandemic, the US faced nationwide shortages of nasopharyngeal swabs due to both overwhelmed supply chains and an increase in demand. To address this shortfall, multiple 3D printed swabs were ultimately produced and sold for COVID-19 testing. In this work, we present a framework for mechanical and functional bench-testing of nasopharyngeal swabs using standard and widely available material testing equipment. Using this framework, we offer a comprehensive, quantitative comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…3D printing technologies provide a new method to solve the supply shortage of commercial NP swabs in the COVID-19 pandemic 10 , 11 . The original 3D-printed NP swabs designed with solid structures with micro convex arrays were verified to be statistically comparable and even replaceable to the commercial NP swabs in sampling effectiveness 10 24 . Compared with the commercial NP swabs of standardized specifications, they can be designed with individualized size and shape to better fit different individuals or various sampling sites 1 , 20 , 25 (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 92%
“…3D printing technologies provide a new method to solve the supply shortage of commercial NP swabs in the COVID-19 pandemic 10 , 11 . The original 3D-printed NP swabs designed with solid structures with micro convex arrays were verified to be statistically comparable and even replaceable to the commercial NP swabs in sampling effectiveness 10 24 . Compared with the commercial NP swabs of standardized specifications, they can be designed with individualized size and shape to better fit different individuals or various sampling sites 1 , 20 , 25 (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 92%
“…It is noteworthy to mention that designs I to VIII are developed at the FAMES Lab of Indiana University, IX-X are Abiogenix designs, XI-XIII are Fanthom designs, XIV is USF Health design and XV-XIX are Wyss designs. Notably, in this study, we included the open-source designs of 3D printed NP swabs for which the CAD files were available and these include designs of Harvard's Beth Israel Deaconess Medical Center, University of Washington, Stanford University, MIT and the United States Army, and Indiana University [ 8 , 9 , 16 , 17 ]. Apart from these designs available in the literature, we also report and consider three novel geometric designs of 3D printed NP swabs developed by our research group that met the FDA-approved design requirements and are shown in Figure 2 .…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Some of the preliminary results of 3D printed NP swabs are quite discouraging, which suggests that conventional swabs outperform the 3D printed swabs [ 8 , 9 ]. The current limitations of the 3D printed NP swabs include inferior quality of the collected samples, inadequate clinical specimens, inappropriate materials (e.g., too sticky or brittle), inappropriate designs (e.g., sharp heads), patient discomfort particularly among kids, and limited mechanical stability, to name a few [ 4 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. It is noteworthy to mention that most of these limitations are directly linked to the huge variability in mucus rheology and nasal cavity geometries in the target population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic has highlighted that additive manufacturing is a dependable and rapid solution for addressing the urgent needs of the health sector, especially when supply chains are disrupted. [1][2][3][4][5][6] In some cases, additive manufacturing has the potential to be a complementary technology to conventional mass production. For example, 3D-printed nasal swabs produced results matching those of the flocked nylon commercial swabs in over 90% of cases.…”
Section: Introductionmentioning
confidence: 99%